Role of Country- and Firm-Level Determinants in Environmental, Social, and Governance Disclosure - Baldini, Maria (Journal of business ethics, 2018)
In recent years, companies receive pressure to release environmental, social, and governance (ESG) disclosure, since these are perceived as critical issues by society. Despite this pressure, ESG disclosure practices considerably vary by firm. Prior academic literature investigated country- and firm-level factors determining such variation, alternatively adopting the institutional and legitimacy theory. By combining these theories in a unique framework, this study investigates the extent to which social structures (i.e., institutional theory) and social legitimization (i.e., legitimacy theory) influence ESG disclosure practices and each pillar. Results obtained using a cross-country sample of 14,174 firm-year observations during 2005–2012 provide evidence that country-level characteristics such as a political system (legal framework and corruption), labor system (labor protection and unemployment rate), and cultural system (Social Cohesion and Equal Opportunities) significantly affect firms’ ESG disclosure practices. However, their impact is heterogeneous in that they either reduce or enhance disclosure levels and may differ by pillar. Results for firm-level characteristics related to a firm’s visibility (analysts coverage, cross-listing, leverage, and size) demonstrate a positive and homogeneous effect on ESG disclosure and each pillar. These results inform policy makers and regulators aiming to enhance ESG disclosure levels of the risk they incur when managing variables related to social structure and the benefits of exposing firms to higher visibility.